Start by writing the equation for magnetic force:

magnetic force = q*v*B

Now write the equation for centripetal acceleration:

a = v^2 / R

Force = m*a

plugging in a we get:

Force = m* v^2 / R

Now set magnetic force equal to force:

q*v*B = m* v^2 / R

Now we need to use K.

K = (1/2)m*v^2

multiplying by 2 this becomes:

2K = m*v^2 , which we can now subsitute into the equation above and get:

q*v*B = 2K / R

Solving for v we get:

v = 2K/ (R*q*B)

Part B, similarly we can calculate mass by using the force equation again:

Force = m*a

and so solving for m we get:

m = Force / a

Where Force = q*v*B furthermore the v can be replaced for what we got in part A.

so Force = q*(2K/ (R*q*B))*B

and a = v^2 / R, furthermore the v can be replaced for what we got in part A.

so a = (2K/ (R*q*B))^2) / R

plugging into the equation for m we get:

m = *q*(2K/ (R*q*B))*B) / (2K/ (R*q*B))^2) / R

after simplifying we get that:

m = (R*q*B)^2 / (2K)